Influence of drying on the chemical composition and bioactivity of Piper aduncum (Piperaceae) essential oil against Aedes aegypti (Diptera: Culicidae) (Research, Society and Development, 2021)
Piper species are producers of essential oils with high yield and promising chemical composition for both perfumery and the pharmaceutical industry. They present bioactivity against pathogens and against insect pests, whether agricultural or medical, such as Aedes aegypti, for example, a vector of arboviruses with a high incidence in tropical and subtropical regions. In this study, an investigation was carried out to elucidate the chemical composition of essential oils from the leaves and inflorescences of Piper aduncum collected in the state of Goiás, Brazil. Evaluating the interference of the drying process on yield, chemical composition and larvicide potential against Ae. aegypti. Leaves and inflorescences of P. aduncum were collected in the rural area of the municipality of Iporá-GO. Fresh and dried samples were processed separately and subjected to hydrodistillation for two hours. The oil obtained was qualitatively evaluated by gas-coupled chromatography and mass spectrometry. Greater yield was observed in samples submitted to the drying process. Oils obtained from fresh samples had a higher percentage of monoterpene hydrocarbons. Variation was observed between the major components of samples of fresh leaves and inflorescences, with eupatoriochrome being the major component in dried samples. Larvicidal activity against Ae. aegypti was considered promising (LC50